Severe acute respiratory disease in health-care workers during the influenza H1N1 pandemic in Argentina - Pryluka, Daniel; Lopardo, Gustavo; Daciuk, Lucia; Stecher, Daniel; Bonvehi, Pablo (The Journal of Infection in Developing Countries, 2013)
Introduction: During the 2009 influenza H1N1virus pandemic, health-care workers were exposed to elevated risk of infection. The aim of this study was to estimate the risk for severe acute respiratory disease (SARD) in this population during the pandemic period in Argentina. Methodology: we conducted a retrospective survey in which all members of the Argentine Society of Infectious Diseases were invited to answer an online survey providing information on health-care staff working at their hospital or health center, who were hospitalized for SARD, between May and August 2009. Results were compared to population-based SARD surveillance data obtained from the Ministry of Public Health. Results: Fifty hospitals completed the survey. Out of a total population of 58,902 health-care workers, 41 were reported to have been hospitalized for SARD (hospitalization rate 69.6/100000), 19 of whom tested positive for H1N1 using real time polymerase chain reaction. Hospitalization rate in the general population during the same time period was 20.3/100000 (p < 0.01), thus indicating increased SARD hospitalization risk in health-care workers (OR 3.1 95% CI: 2.3 - 4.1; p < 0.01). Conclusions: During the 2009 pandemic, health-care workers in Argentina suffered increased risk of hospitalization due to SARD compared to the general population. We recommend immunization of all personnel, as well as enforcing stricter infection control measures in hospitals to prevent future transmission of influenza H1N1virus.